Formation of plastic properties of 12Cr18Ni10Ti steel highly irradiated by neutrons - Maksimkin, О.P.; Merezhko, D.А.; Merezhko, М.S.; Sarsenbayeva, K.B. (Вопросы атомной науки и техники, 2021)
New results of the experiments on the study of nature and patterns of the effect of anomalously high ductility of austenitic meta-stable irradiated steels are discussed, the possible causes of its formation and the relationship with the deformation “wave” are analyzed, and the recommendations for “wave” modeling are provided in the paper.